ANALISA FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT MENGGUNAKAN VIDEO CONFERENCING DI ERA PANDEMI COVID-19 - Harminingtyas, Rudika; Widodo, Untung (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2022)
In the new normal era, the use of video conferencing technology continues to increase because activities using video conferencing have become a new habit among Indonesian people. However, despite a significant increase, the factors that influence the interest in reusing video conferencing technology after the new normal era are still a question. Thus, this study aims to create a research model to explain what factors have a positive influence on the interest in reusing video conferencing technology such as perceived ease of use, perceived usefulness, self-efficacy, perceived enjoyment, social influence, facilitating conditions and user satisfaction. By using quantitative research methods, the population in this study was taken from people who live in the Semarang and surrounding areas with a total of 100 samples collected using purposive sampling method through questionnaires from google form. Then the data is processed using Smart PLS 3.3.3. Meanwhile, the results of data analysis using the structural equation modeling method show that all variables have a significant direct relationship except the relationship between the variable perveive ease of use and continuity intention which has an insignificant relationship.Keyword : Video Conferencing; TAM; perceived ease of use; perceived usefulness; continuance intention